PLAN OF ACTIONS TO PREVENT, CONTROL AND DESINFECT CONTAMINATED PRODUCTS OF FUNGI AND AFLATOXINS - Armijo C., J. (2009)
Aflatoxins, a group of highly toxic substances produced by certain species of Aspergillus, especially A. flavus, have been found to occur in agricultural products such as corn, peanuts, cotton seed, animal feed, and many varieties of nuts. Experimental studies show that aflatoxins are carcinogenic. This paper proposes a plan of actions to prevent, control and desinfecting products contaminated with aflatoxins. Post harvest treatment of the product involves drying and storage temperature of 5 °C and relative humidity below 80%. The technique of ozone gas to disinfect contaminated products represents the best alternative because does not generate waste, the product is not damaged and the ozone gas is safe.